Perdebatan Aspek-Aspek Ketuhanan Dalam Teologi Islam Dan Kaitannya Dengan Kalimat Tauhid - Abdillah Abdillah (Al-Hikmah Journal for Religious Studies, 2014)
In Islam, the divinity matters is one of the core points of delegating Muhammad saw. It aims to consolidate the oneness of God (tauhidullah. La ilaha illallah) that there is no God but Allah Swt. 13 years after Muhammad saw was delegated in Makkah, it was one of purification of aqidah from reliance of Arabian to their ancestral worshiped at the time in line with thought paradigm which spreads in many centuries. The controvercy of mutakkallimin in any aspects of divinity have appeared the disputation of history of Islamic theology. In the context of tauhid, it has spur on Moslems paradigm in facing various development. Furthermore, it can become studies foundation paradigm in comprehending the divinity and acknowledging the oneness of God. All of the controvertions in scholarly storage of Islam will direct to those factors. Eventhough, it has caused negative impacts in one side, but it has contributed lot of benefits to the history and culture of Moslem.